2009
DOI: 10.1126/science.1175141
|View full text |Cite
|
Sign up to set email alerts
|

Band Formation from Coupled Quantum Dots Formed by a Nanoporous Network on a Copper Surface

Abstract: Coupled Copper Surface States Periodic arrays of quantum dots can create new electronic states that arise from coupling of the states created by confinement. Lobo-Checa et al. (p. 300 ) show that the electronic surface-state of copper can be converted into a regular array of quantum dots. An organic overlayer that is created on the copper surface has pores 1.6 nanometers in diameter that trap the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
186
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(200 citation statements)
references
References 28 publications
(35 reference statements)
13
186
1
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11] The nanostructures that scatter surface-state electrons can be built by scanning tunneling microscope (STM) manipulation of adatoms or molecules [1][2][3][4][5] or by self-assembly processes. [6][7][8][9][10][11] In recent years, the concepts of supramolecular coordination chemistry have been used to build two-dimensional systems through surface-assisted coordination assembly. 12,13 Highly ordered nanostructures consisting of metal atoms and organic molecules can form on surfaces according to well-defined metal-ligand coordination.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] The nanostructures that scatter surface-state electrons can be built by scanning tunneling microscope (STM) manipulation of adatoms or molecules [1][2][3][4][5] or by self-assembly processes. [6][7][8][9][10][11] In recent years, the concepts of supramolecular coordination chemistry have been used to build two-dimensional systems through surface-assisted coordination assembly. 12,13 Highly ordered nanostructures consisting of metal atoms and organic molecules can form on surfaces according to well-defined metal-ligand coordination.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] Perylene derivatives sublimated under vacuum have the ability to self-assemble on at metal surfaces and to form two-dimensional hydrogen-bonded nanoarchitectures. [11][12][13][14][15][16][17] These molecules can also form multicomponent organic structures when mixed with complementary building blocks. [18][19][20][21][22] Perylene derivatives are thus very attractive to fabricate new devices as new organic at-heterojunction solar cells for example.…”
mentioning
confidence: 99%
“…Some examples on Cu(111) in- clude NC-Ph5-CN, 3deh-DPDI, and dehydro-DPDI [26][27][28][29]; Br-DNT on Ag(111) is another [30]. In all these cases, there is a single molecule on edge of the hexagonal pores.…”
Section: Honeycomb Netsmentioning
confidence: 99%
“…Lobo-Checo et al [26] observed a large regular honeycomb of DPDI on Cu(111). With scanning tunneling spectroscopy (STS) they found a new peak 0.22 eV below threshold characteristic of a confined dot state.…”
Section: Comparison With Other Honeycomb Structuresmentioning
confidence: 99%
See 1 more Smart Citation